OLDER PEOPLE'S DIGITAL LIVES - Bossio, Diana; Grønning, Anette; Cabalquinto, Earvin; Milne, Esther; Schleser, Max; McCosker, Anthony; Albury, Kath (AoIR Selected Papers of Internet Research, 2020)
Drawing from a conceptual framework that problematises and redefines the digital lives of older people aged 65 years and over, this panel explores how older people engage with digital communication tools and skills, and the way this plays out in their everyday lives. Each paper situates older people as experiencing a rich social life integrated with digital technologies and understood in terms of multi-faceted disparities in internet use, skills and modes of digital participation. How older people’s digital lives are negotiated and developed, and the particular frustrations and barriers to their digital participation, are situated as particular to their cultural context for use of communication tools. This panel thus contributes new understanding of how older people’s digital lives are emerging, moving away from simplistic descriptions of skills, to the multi-faceted and complex negotiations occurring when older people make decisions about connecting with digital tools.